PELATIHAN PENGGUNAAN GOOGLE DRIVE SEBAGAI MEDIA MANAJEMEN ARSIP BAGI PERANGKAT DESA DI DESA PANGGUNG KECAMATAN PELAIHARI - Jaka Permadi; Hendrik Setyo Utomo; Eka Wahyu Sholeha (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2021)
The Panggung village officials in carrying out its performance has problems in archive management. Files stored in personal computers can be lost and corrupted due to a number of factors. Another problem is the difficulty of sharing files via social media such as WhatsApp, especially if the size is large. Finding files that have been shared for a long time is also difficult. Training on the use of Google Drive was carried out as a solution to the problem of archive management in Panggung Village. This training was wrapped in the form of community service and was held on June 2nd, 2021 at the Panggung Village Office which was attended by 20 Panggung village officials. The training is divided into four training materials: introduction to Google Drive, storing documents in Google Drive, sharing files and folders, and collaborating in managing documents on Google Drive. At the end of the training participants were asked to fill out a service partner satisfaction questionnaire. As a result, 93.5% of participants stated that they were very satisfied with the training. The remaining of them, about 6% of participants said that they were satisfied and 0.5% of participants said that they were not satisfied.